221k views
4 votes
Please someone solve this

Please someone solve this-example-1
User Todd M
by
5.3k points

1 Answer

4 votes

Answer:

a)

(4a - 3b + 4) + (a + 3b - 1) =

4a - 3b + 4 + a + 3b - 1 =

5a + 3

b)

(2x^2 - 3x - 3) + (-x^2 - 6x + 8) =

2x^2 - 3x - 3 - x^2 - 6x + 8 =

x^2 - 9x + 5

c)

(3m^2 + 5m - 6) + (-m^2 - 4n + 5) =

3m^2 + 5m - 6 - m^2 - 4n + 5 =

m^2 + 5m - 4n -1

d)

(4x^3 - 3xy^2) + (x^3 - 5xy^2 - 5y^2) =

4x^3 - 3xy^2 + x^3 - 5xy^2 - 5y^2 =

7x^3 - 8xy^2 - 5y^2

e)

(5m + 2lm) + (l^2 - 3m^2 - 2lm) =

5m + 2lm + l^2 - 3m^2 - 2lm =

5m + l^2 - 3m^2

User Jackssn
by
4.7k points